Optimization Of Composting Time from Palm Fronds and Empty Buttons Of Palm Oil (Elaeis guineensis Jacq) with Various Bioactivators - Ali Mustafa Silalahi; Ryan Firman Syah; Pauliz Budi Hastuti (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Composting or decomposition is a method of processing solid waste which has a high content (70% -80%). Empty fruit bunches from the processing of Crude Palm Oil Factories and fronds of palm oil (TM) plants have the potential to be used as organic fertilizer. Composting without a decomposer takes a long time of seven months, so a bio activator is needed to speed up the process. Research with the aim of determining the influence of various bio activators in accelerating the composting of palm fronds and empty bunches has been carried out at PT. Bahana Karya Semesta unit of Sungai Air Jernih Estate, Pauh, Sarolangun, Jambi in November 2021-February 2022. The Research method used was a Complete Randomized Design (RAL) with two factors. The first factor is bioactivator consisting of four types such as LCPKS (liquid waste from crude palm oil factory), MOL (Local microorganism), EM4 (Effective microorganism 4) and cow dung. The second one is the compost material consisting of empty fruit bunch/EFB (5 kg), fronds (5 kg), EFB + fronds (2.5 kg + 2.5 kg), EFB + fronds + LCC (legume cover crop) (2 kg + 2kg + 1kg). C/N ratio, temperature, campiness, shrinkage, crumbly, and color of compost were also recorded. The results showed that the bio activator could decompose organic material with some of the parameters that we measured. The analysis of the C/N ratio showed that each treatment gave different results. Palm fronds + LCPKS had the highest C/N ratio of 91, meanwhile, the combination of EFB+cow dung showed the lowest C/N ratio of 23. The material of EFB + fronds + LCC showed the highest pH value of 6.36 and the highest compost depreciation of 57.48%. The variety of compost material has the same influence on the temperature, campiness, and color of the compost. Meanwhile, the type of bio activator had the same effect on temperature, pH, shrinkage, crumbly, and color of the compost.